Strengthening local autonomy in development: composite budgeting, expenditure planning and implementation in Nanumba South district, Ghana (Commonwealth Journal of Local Governance, 2024)
Including local citizens in decision-making about the use of local resources is crucial to improving the generation of locally raised funds. This study illustrates the positive effects of composite budgeting – a participatory process – in meeting local people’s development interest and needs, and in promoting expenditure autonomy. Using a case study approach and drawing on both qualitative and quantitative data, the study found that Ghana’s system of district assemblies – which are largely made up of elected members – appears to be relatively successful in delivering the capacity and independence required to make funding decisions that benefit local people and the development of their area. The paper suggests a link between citizens’ confidence in the working of their assembly and their willingness to contribute to locally generated funds.